Follow-Up for an Abnormal Newborn Screen for Severe Combined Immunodeficiencies (NBS SCID): A Clinical Immunology Society (CIS) Survey of Current Practices - Vijaya Knight; Jennifer R. Heimall; Nicola Wright; Cullen M. Dutmer; Thomas G. Boyce; Troy R. Torgerson; Roshini S. Abraham (MDPI AG, 2020)
Severe combined immunodeficiency (SCID) includes a group of monogenic disorders presenting with severe T cell lymphopenia (TCL) and high mortality, if untreated. The newborn screen (NBS) for SCID, included in the recommended universal screening panel (RUSP), has been widely adopted across the US and in many other countries. However, there is a lack of consensus regarding follow-up testing to confirm an abnormal result. The Clinical Immunology Society (CIS) membership was surveyed for confirmatory testing practices for an abnormal NBS SCID result, which included consideration of gestational age and birth weight, as well as flow cytometry panels. Considerable variability was observed in follow-up practices for an abnormal NBS SCID with 49% confirming by flow cytometry, 39% repeating TREC analysis, and the remainder either taking prematurity into consideration for subsequent testing or proceeding directly to genetic analysis. More than 50% of respondents did not take prematurity into consideration when determining follow-up. Confirmation of abnormal NBS SCID in premature infants continues to be challenging and is handled variably across centers, with some choosing to repeat NBS SCID testing until normal or until the infant reaches an adjusted gestational age of 37 weeks. A substantial proportion of respondents included naïve and memory T cell analysis with T, B, and NK lymphocyte subset quantitation in the initial confirmatory panel. These results have the potential to influence the diagnosis and management of an infant with TCL as illustrated by the clinical cases presented herein. Our data indicate that there is clearly a strong need for harmonization of follow-up testing for an abnormal NBS SCID result.